Evaluation of transport policy packages in the excess commuting framework: The case of Xiamen, China. (April 2019) - Xu, Wangtu (Ato); Yang, Linchuan; Zhang, Wei
Abstract: Transport policies are often carried out in package form, but, presently, transport policy package (TPP) remains a theoretical concept whose practicality has rarely been investigated. Additionally, jobs-housing balance has become a major urban planning and public policy issue that has received considerable scholarly attention. This study probes into evaluating TPPs using the minimum commute, a proxy for jobs-housing balance and an important statistic in the excess commuting framework. Using a brief transportation problem model of linear programming, the minimum commute statistics in scenarios with different TPPs are calculated by repeatedly solving the proposed mathematical model. Moreover, this study considers multimodal commuting for better reflecting realistic situations. Drawing on an empirical study in Xiamen, China, we show that the mathematical model provides indicators for urban form evaluation. Highlights: Assesses the effect of transport policy packages on the theoretical minimal commuting cost Proposes a transportation problem model of linear programming to determine the effect Integrates multimodal commuting into the excess commuting framework